CALCULATION OF A CYLINDRICAL WELL BY THE NUMERICAL-ANALYTICAL BOUNDARY ELEMENT METHOD - Surianinov, M.; Surianinov, V. (Municipal economy of cities. Series: «Economy science», 2025)
An algorithm for applying the numerical-analytical boundary element method to the calculation of reinforced concrete and fiber-reinforced concrete cylindrical wells has been developed. Elements of round or annular cross-section are used in many engineering structures, such as pressure and non-pressure pipes, power line supports, water towers, wells for various purposes, etc. Modern construction requires new effective materials. One of them is steel-fiber concrete, which allows to improve such characteristics of concrete as crack resistance, frost resistance, tensile strength, bending, torsion, etc. The use of fiber allows to change the nature of the destruction process. Unlike conventional concrete, in which this process occurs almost instantly, brittle destruction does not occur in fiber-reinforced concrete, and the structure continues to resist the load, and the nature of the destruction changes from brittle to ductile. Methods for calculating concrete and fiber-reinforced concrete wells are the subject of many studies. A special place is occupied by cylindrical wells, which from the point of view of structural mechanics are long cylindrical shells. Analysis of the literature shows that the development of new methods for calculating reinforced concrete and steel-fiber-reinforced concrete cylindrical shells is given very little attention, so this direction is quite relevant. The solution of the problem by the proposed method is reduced to solving one system of linear algebra equations and calculating the stress-strain state at the internal points of the rods by the ratio of the initial parameter method. Such a solution scheme provides very accurate and reliable results that can be presented using MATLAB or another environment. The implementation of the proposed method allows you to obtain kinematic and static parameters of the stress-strain state of the shell of reinforced concrete or fiber-reinforced concrete cylindrical wells under any loads and boundary conditions. In the future, the authors plan to solve the problem using the finite element method in some engineering program (for example, in the ANSYS package) in order to assess the accuracy of the developed algorithm.